Gestação e parto na adolescência: mecanismos maternos e fetais - Almeida, Luana Araujo [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
The lack of information on factors of sexual and reproductive education on the part of adolescents may imply in the non-acquisition of contraceptive methods, which increases the chances of an unplanned pregnancy at this stage of life. Furthermore, it is at this stage that puberty occurs, where boys and girls begin to notice differences in their bodies due to hormonal changes. In addition, the undergraduate biological sciences course includes a supervised curricular internship, which aims to contribute to the education of undergraduates. Thus, the present work was based on the realization of some classes for first year high school students, in order to assist in the learning of adolescents about the factors involving the biological mechanisms of pregnancy, STIs, anatomy and physiology of the reproductive system, puberty and adolescence, aiming to contribute to responsible motherhood and fatherhood, as well as the professional maturation of the undergraduate student. During the remote classes there was low student attendance in class, but the situation improved with the return of the face-to-face classes. Moreover, based on the feedbacks, the students demonstrated that the content was very relevant for their education, that they acquired new knowledge, and that they were able to understand the information presented. Finally, it is considered that the project's objectives were achieved, since the undergraduate student was able to experience the school environment and develop professional maturity. Furthermore, based on the students' participation in the classroom and in the evaluation answers, the project classes were also able to help students learn about the biological mechanisms of pregnancy, puberty and adolescence, STIs, among others.

A falta de informação sobre fatores da educação sexual e reprodutiva por parte dos adolescentes pode implicar na não aquisição de métodos contraceptivos, o que aumenta as chances de uma gravidez não planejada nesta etapa da vida. Para mais, é nesta fase que ocorre a puberdade, onde meninos e meninas começam a notar diferenças em seus corpos decorrentes das alterações hormonais. Além disso, a grade do curso de licenciatura em ciências biológicas conta com o estágio curricular supervisionado, que tem como objetivo contribuir com a formação dos licenciados. Com isso, o presente trabalho se baseou na realização de algumas aulas para alunos do primeiro ano do ensino médio, a fim de auxiliar na aprendizagem dos adolescentes quanto aos fatores que envolvem os mecanismos biológicos da gravidez, ISTs, anatomia e fisiologia do sistema reprodutor, puberdade e adolescência, visando contribuir com a maternidade e paternidade responsável, além do amadurecimento profissional da licencianda. Durante as aulas remotas houve baixa presença dos alunos em aula, mas a situação melhorou com a volta das aulas presenciais. Além disso, com base nos feedbacks, os estudantes demonstraram que o conteúdo trabalhado foi de grande relevância para suas formações, que adquiriram conhecimentos novos e que conseguiram entender as informações expostas. Por fim, considera- -se que os objetivos do projeto foram alcançados, visto que a licencianda pôde vivenciar experiências no ambiente escolar e desenvolver amadurecimento profissional. Ademais, com base na participação dos alunos em sala de aula e nas respostas da avaliação, as aulas do projeto também conseguiram auxiliar na aprendizagem dos alunos quanto aos mecanismos biológicos da gravidez, puberdade e adolescência, ISTs, entre outros.
Pregnancy and childbirth in adolescence: maternal and fetal mechanisms
Keywords: Pregnancy; Adolescence; Puberty; Reproductive system; Gravidez; Puberdade; Adolescência; Aparelho genital